2013
DOI: 10.1186/2050-6511-14-6
|View full text |Cite
|
Sign up to set email alerts
|

Glibenclamide inhibits cell growth by inducing G0/G1 arrest in the human breast cancer cell line MDA-MB-231

Abstract: BackgroundGlibenclamide (Gli) binds to the sulphonylurea receptor (SUR) that is a regulatory subunit of ATP-sensitive potassium channels (KATP channels). Binding of Gli to SUR produces the closure of KATP channels and the inhibition of their activity. This drug is widely used for treatment of type 2-diabetes and it has been signaled as antiproliferative in several tumor cell lines. In previous experiments we demonstrated the antitumoral effect of Gli in mammary tumors induced in rats. The aim of the present wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
36
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(42 citation statements)
references
References 51 publications
5
36
1
Order By: Relevance
“…In the current study, Gli previous treatment was also inhibited tumour growth in rats bearing Walker-256 cancer cells. The literature shows that Gli inhibits cell growth by inducing G0/G1 arrest in the human breast cancer, cell line mda-mb-231 [28-30]. Indeed, for the first time, our findings show that chronic treatment with Gli is capable of protecting both control and prediabetic obese MSG-rats against tumour growth, even when Gli treatment was stopped one day before tumour cell grafts.…”
Section: Discussionsupporting
confidence: 48%
See 2 more Smart Citations
“…In the current study, Gli previous treatment was also inhibited tumour growth in rats bearing Walker-256 cancer cells. The literature shows that Gli inhibits cell growth by inducing G0/G1 arrest in the human breast cancer, cell line mda-mb-231 [28-30]. Indeed, for the first time, our findings show that chronic treatment with Gli is capable of protecting both control and prediabetic obese MSG-rats against tumour growth, even when Gli treatment was stopped one day before tumour cell grafts.…”
Section: Discussionsupporting
confidence: 48%
“…Several studies have demonstrated the effects of Gli on tumour growth arrest in different cancer types [27, 28, 37]. It has been shown that different subtypes of potassium channels are involved in normal and malignant cell proliferation [38].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We previously demonstrated that Ishige sinicola , a brown alga, or minoxidil, could increase the levels of cyclin E and CDK2, but decreased the level of the p27 kip1 , a CDK inhibitor in dermal papilla cells [36]. This was further supported by the observation that glibenclamide, a K ATP channel blocker, inhibited cell proliferation, which was accompanied by an increase in cell cycle arrest and the p27 kip1 level [37]. These results suggested that U. peterseniana extract increased the proliferation of dermal papilla cells through the progression of the cell cycle by the alteration of the level of cell cycle proteins.…”
Section: Discussionmentioning
confidence: 93%
“…Glibenclamide was the first second-generation sulfonylurea drug, and it functions by targeting sulfonylurea receptors (SURs). To date, a number of studies have indicated that glibenclamide can inhibit the growth of various types of cancer (51)(52)(53)(54); however, the antitumor mechanisms have not been fully elucidated. In recent years, certain studies have focused on potassium (K + ) channels, which are involved in physiological cellular functions, including insulin release, cell proliferation, and apoptosis.…”
Section: Selection Comparability Outcome ----------------------------mentioning
confidence: 99%